1996
DOI: 10.1093/clinids/22.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Severe Infection Due to Actinomyces bernardiae: Case Report

Abstract: We describe a patient with a serious urinary tract infection due to Actinomyces bernardiae (formerly classified as CDC [Centers for Disease Control and Prevention, Atlanta] fermentative coryneform group 2). Our patient had long-standing bladder dysfunction and developed hydroureteronephrosis, renal lithiasis, perirenal abscesses, and septicemia. A. bernardiae is distinct from Actinomyces pyogenes and several CDC coryneform groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 0 publications
0
17
0
4
Order By: Relevance
“…bernardiae has been described as a pathogen in urinary tract infections (Ieven et al, 1996;Lepargnear et al, 1998), joint infections (Adderson et al, 1998;Bemer et al, 2009;Lo ez et al, 2009), skin and soft-tissue infections (Weitzel et al, 2011;Otto et al, 2013), necrotizing fasciitis (Clarke et al, 2010) and a case of eye infection (Funke et al, 1995). Six strains of T. bernardiae have been cultured from blood specimens, but no deaths due to T. bernardiae have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…bernardiae has been described as a pathogen in urinary tract infections (Ieven et al, 1996;Lepargnear et al, 1998), joint infections (Adderson et al, 1998;Bemer et al, 2009;Lo ez et al, 2009), skin and soft-tissue infections (Weitzel et al, 2011;Otto et al, 2013), necrotizing fasciitis (Clarke et al, 2010) and a case of eye infection (Funke et al, 1995). Six strains of T. bernardiae have been cultured from blood specimens, but no deaths due to T. bernardiae have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since some coagulase-negative species can be distinguished only by a limited number of stable biochemical tests, the precise assignment of a staphylococcal strain to a species is difficult to obtain. What is more, atypical characteristics such as phosphatasenegative reactions in certain Staphylococcus epidermidis strains often result in their misidentification as Staphylococcus hominis (Ieven et al, 1995). Fatty acid compositions of coagulase-negative staphylococcal species showing quantitative but not qualitative differences in certain acids are applied for their identification (Kotilainen et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…bernardiae is a gram-positive bacillus that forms part of the normal microbiota of human skin and the oropharynx. Few cases of infection due to this microorganism in pure culture have been reported until now (4)(5)(6)(7)(8)(9)(10)(11)(12), and 5 additional cases have been reported as causing mixed infections ( Table 1). The true incidence of infections with this bacterium is unknown because when isolated in clinical samples, these coryneform bacteria are not identified.…”
Section: Infections Due To Trueperella Bernardiaementioning
confidence: 99%
“…Some studies have shown that T. bernardiae is susceptible to all antimicrobial drugs tested, except for ciprofloxacin (4,15). However, other studies show resistance to clindamycin and erythromycin (9), norfloxacin and fosfomycin (13), metronidazole (6), pefloxacin (5), and penicillin G (7).…”
Section: Infections Due To Trueperella Bernardiaementioning
confidence: 99%